Practical Video Game Bots Automating Game Processes using C++, Python, and AutoIt - Shpigor, Ilya (Apress, 2018)
Develop and use bots in video gaming to automate game processes and see possible ways to avoid this kind of automation. This book explains how bots can be very helpful in games such as multiplayer online games, both for training your character and for automating repetitious game processes in order to start a competition with human opponents much faster. Some players might use bots for cheating or avoiding game rules to gain an advantage over opponents - a sophisticated form of hacking that includes some elements of artificial intelligence (AI). However, while Practical Video Game Bots considers these topics, it is not a cheater's guide. Rather, this book is an attempt to overcome the information vacuum regarding bot development in video game applications. Through the use of three case study game examples, it covers most methods and technologies that are used by bot developers, and the details of anti-cheating systems. This book provides answers and useful advice for topics such as process automation, reverse engineering, and network applications. Modern bot applications use technologies from all these domains. You will also consider the work mechanisms of different kinds of bots and will write simple prototypes. You will: Discover bots and apply them to game applications Use clicker bots with OS-level embedding data, output-device capture, and more Develop in-game bots, with process memory analysis and access Work with out-game bots, with network interception and embedding data Deal with input device emulation and OS-level interception data.